The Pakistan Development Review (JSTOR)
The journal is issued quarterly and, with a fair mix of topics, regularly contains original (theoretical and empirical) contributions to Economics, in general, and on Pakistan?s socio-economic problems, in particular. Nearly every issue carries contributions by scholars from Pakistan and overseas.
Keywords: Business, Business & Economics, Development Studies, Economics